Breastmilk Lipids and Oligosaccharides Influence Branched Short‐Chain Fatty Acid Concentrations in Infants with Excessive Weight Gain. Issue 3 (7th January 2020) - Pekmez, Ceyda Tugba; Larsson, Melanie Wange; Lind, Mads Vendelbo; Vazquez Manjarrez, Natalia; Yonemitsu, Chloe; Larnkjær, Anni; Bode, Lars; Mølgaard, Christian; Michaelsen, Kim F.; Dragsted, Lars Ove
Abstract : Scope: The aim is to identify breastmilk components associated with fecal concentration of SCFAs and to investigate whether they differ between infants with high weight gain (HW) and normal weight gain (NW). Methods and results: Breastmilk and fecal samples are collected from mother–infant dyads with HW ( n  = 11) and NW ( n  = 15) at 5 and 9 months of age. Breastmilk is profiled on ultra‐performance LC‐quadrupole TOF‐MS platform. Fecal SCFAs are quantified using an isotope‐labeled chemical derivatization method. Human milk oligosaccharides (HMOs) are quantified using HPLC after fluorescent derivatization. Lower levels of α‐linolenic acid, oleic acid, 3‐oxohexadecanoic acid, LPE (P‐16:0), LPC (16:0), LPC (18:0), PC (36:2) in breastmilk from mothers from the HW‐group at 5 months of age is found. Fecal SCFA concentrations are increased during the transition period from breastfeeding to complementary feeding. Fecal butyrate concentration is higher in the NW‐group at 9 months of age. Fecal branched SCFAs are positively associated with breastmilk phospholipid levels, free‐fatty acid levels, HMO‐diversity, sialylated‐HMOs, 6′‐sialyllactose, and disialyl‐lacto‐ N ‐hexaose. Conclusion: Fecal branched SCFA concentrations seem to be affected by breastmilk lipid and HMO composition. These differences in breastmilk metabolites may partially explain the excessive weight gain in early life. Abstract : The breastmilk phospholipid, free fatty acid, and oligosaccharide levels are associated with fecal branched short‐chain fatty acid concentrations in infants. The infants with excessive weight gain receive breastmilk with lower human milk oligosaccharide diversity and lower levels of α‐linolenic acid, oleic acid, and some phospholipid species at five months of age, which may partially explain excessive weight gain in early life.